2017
DOI: 10.1159/000478850
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Care Needs in the Oldest Old Primary Care Patients with Cognitive Disorders: Results of the AgeCoDe and AgeQualiDe Study

Abstract: Background: In the future, an increase in health care needs in the elderly is expected. Reports on unmet care needs of the oldest old with cognitive disorders are pending. This study aims at exploring unmet needs in the oldest old primary care patients with mild cognitive impairment (MCI) and dementia. Furthermore, the association between sociodemographic and clinical factors and unmet needs ought to be analyzed. Methods: Based on the study “Needs, Health Service Use, Costs and Health-Related Quality of Life i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
2
7
0
2
Order By: Relevance
“…In line with this, our study suggests that loss experiences are strongly associated with a higher number of unmet psychological and physical care needs after holding other factors constant. Our study also confirms previous results on risk factors for increased unmet needs including a higher age, marital status, depression, decreased social engagement and more severe morbidity [ 15 , 25 , 41 43 ]. Thus, the current and earlier findings highlight the importance of the implementation of tailored intervention programs targeting at high-risk older adults with recent loss experiences.…”
Section: Discussionsupporting
confidence: 92%
“…In line with this, our study suggests that loss experiences are strongly associated with a higher number of unmet psychological and physical care needs after holding other factors constant. Our study also confirms previous results on risk factors for increased unmet needs including a higher age, marital status, depression, decreased social engagement and more severe morbidity [ 15 , 25 , 41 43 ]. Thus, the current and earlier findings highlight the importance of the implementation of tailored intervention programs targeting at high-risk older adults with recent loss experiences.…”
Section: Discussionsupporting
confidence: 92%
“…Some predisposing and enabling PWD and caregiver characteristics were also independently associated with unmet needs in care recipients. Less education, less income and non-white race are factors that we and others (Black et al, 2013;Hinrichsen and Ramirez, 1992;Scholzel-Dorenbos et al, 2010;Zhor et al, 2018;Stein et al, 2017) have previously identified as significant correlates of unmet needs in PWD. Education and income may be enabling factors for obtaining information on and/or access to dementia-related services.…”
Section: Discussionsupporting
confidence: 50%
“…In terms of needs assessment, there are often discrepancies in perspectives of different assessors. As shown in this study, typically, community-dwelling people with dementia report a significantly lower number of (unmet) needs than their informal carers 2628. The causes of such discrepancy could be as follows: being unaware of difficulties, lacking knowledge regarding the existence of services, barriers to accessing them, and unsatisfactory service offerings.…”
Section: Discussionmentioning
confidence: 67%